2015
DOI: 10.1097/yic.0000000000000092
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of paliperidone ER in patients with unsatisfactorily controlled schizophrenia by other antipsychotics

Abstract: This study evaluates the effectiveness of paliperidone ER in patients with symptomatic but not highly acute schizophrenia in terms of efficacy, safety, and patients’ perception of their social functioning and well-being. This is a multicenter, open-label prospective study with a flexible-dose approach; 133 patients were enrolled and followed for 13 weeks after switching to paliperidone ER. Outcome efficacy measures were as follows: the Positive and Negative Syndrome Scale (PANSS), the Clinical Global Impressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
5
1
Order By: Relevance
“…Notably and in contrast to our finding of a consistent association between patients’ subjective well-being and functioning, the DAI total score did not correlate with the GAF score at any time point, which corroborates previous findings [ 47 ]. However, in contrast to previous reports we did not find a correlation between the SWN-K and DAI total scores [ 48 , 49 ]. Next to differences in the patient samples studied, this contradictory result can be explained by the scales‘ varying scopes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Notably and in contrast to our finding of a consistent association between patients’ subjective well-being and functioning, the DAI total score did not correlate with the GAF score at any time point, which corroborates previous findings [ 47 ]. However, in contrast to previous reports we did not find a correlation between the SWN-K and DAI total scores [ 48 , 49 ]. Next to differences in the patient samples studied, this contradictory result can be explained by the scales‘ varying scopes.…”
Section: Discussioncontrasting
confidence: 99%
“…The DAIs‘ strength lies in measuring compliance and attitudes towards antipsychotic treatment, whereas the SWN-K can be seen as an alternative for a quality of life instrument in patients using antipsychotic medication [ 48 ]. One previous study [ 49 ] examined a very heterogeneous sample encompassing patients receiving first- and new-generation antipsychotics in different formulations (oral versus long-acting injectable drugs) with 60% of patients having been on the current medication for at least one year. Furthermore, symptom severity has not been reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This also applied to self-assessment on functioning. Although the Subjective Well-Being Under Neuroleptics scale developed by Dieter Naber [ 16 ] was used in several studies (e.g., [ 17 ]) together with the PSOP, we did not find studies dealing with their relationship. Therefore, our result is of special interest.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 70% of the 212 patients enrolled in this study had clinical improvement in psychotic symptoms, as demonstrated by ≥30% improvement in mean PANSS scores (p < 0.0001) [61]. Another study, by Mauri et al, explored the effectiveness of switching to flexible doses of paliperidone ER from other antipsychotic regimens [63]. A total of 110 of the 133 patients were analyzed after the application of exclusion criteria such as inability to swallow oral medication.…”
Section: Safety and Efficacymentioning
confidence: 97%
“…A total of 110 of the 133 patients were analyzed after the application of exclusion criteria such as inability to swallow oral medication. They found that patients had improvement in multiple scoring measures, including the PANSS, PSP and CGI-S scales when using paliperidone ER [63]. Furthermore, patients who have failed therapy on other long-acting or commonly used depot therapies can benefit from paliperidone palmitate injections.…”
Section: Safety and Efficacymentioning
confidence: 99%